Two-component waterproof real stone paint and preparation method thereof

By using two-component waterproof real stone paint and using pure acrylic emulsion and low-alkali cement, the problem of poor waterproof performance of real stone paint coating is solved, significantly improving the waterproof performance and durability of the coating, ensuring the safety and stability of the wall.

CN119859444AActive Publication Date: 2025-04-22HEBEI JINYE COATING TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510058975.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-22
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The existing real stone paint coating has poor waterproof performance and is prone to bulging and falling off after soaking in rainwater, affecting the actual application effect and posing safety hazards.

Method used

Two-component waterproof real stone paint is used, including components A and components B. Component A consists of pure acrylic emulsion, pigment, wetting and dispersing agent, defoaming agent, thickening agent, pH adjuster, bactericidal preservative, film forming additive and aggregate, and component B is low-alkali cement. Through reasonable proportions and additive adjustment, the viscosity, stability and waterproofing of the coating are improved.

Benefits of technology

It significantly improves the waterproof performance of real stone paint, reduces the chance of the coating falling off under rainwater erosion, extends the water and alkali resistance of the coating, and ensures the protection of the wall under natural erosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the field of building decoration materials, in particular to a two-component waterproof real stone paint and a preparation method thereof. The double-component waterproof real stone paint comprises a component A and a component B, wherein the component A comprises the following raw materials in percentage by weight: 30-40% of pure acrylic emulsion, 1-5% of pigment, 0.2-1% of a wetting dispersant, 0.2-1% of a defoaming agent, 0.2-2% of a thickening agent, 0.1-1% of a pH regulator, 0.1-0.2% of a bactericidal preservative, 0.5-2% of a coalescing agent, 40-60% of aggregate and the balance of water; the component B is low-alkali cement; the weight ratio of the component A to the component B is (9.5-10.5): 1. The water absorption capacity of the obtained coating is as low as 1.02-0.01 g / 2 h, the water resistance can reach 290-420 h, and the alkali resistance can reach 102-120 h.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of building decoration materials, and in particular to a two-component waterproof real stone paint and a preparation method thereof. Background Art

[0002] Real stone paint is a kind of paint with natural stone decorative effect. Real stone paint has rich colors and strong coloring properties, which can create a harmonious and elegant architectural atmosphere. It has strong fire resistance and corrosion resistance, and has a wider environmental adaptability than traditional architectural paints, making it widely used in exterior walls. As one of the exterior wall paints with the fastest market demand growth, real stone paint is increasingly favored by the market.

[0003] Real stone paint is generally composed of emulsion components, natural coloring stone powder, functional additives and water. The proportion of various raw materials will affect the performance and quality of real stone paint. At present, a common problem of real stone paint coatings on the market is poor waterproof performance. Real stone paint is generally installed on the facade of a building and is often washed by rain. Poor waterproof performance will cause it to bubble and fall off easily after being soaked in rain, which affects its effect in practical applications and poses a safety hazard. Therefore, the development of a real stone paint with excellent waterproof performance is the focus of current research. Summary of the invention

[0004] In order to improve the waterproof performance of real stone paint and reduce the probability of bulging and falling off of real stone paint, the present application provides a two-component waterproof real stone paint and a preparation method thereof.

[0005] In a first aspect, the present application provides a waterproof real stone paint, which adopts the following technical solution.

[0006] A two-component waterproof real stone paint, including component A and component B:

[0007] The component A comprises the following raw materials in weight percentage: 30-40% pure acrylic emulsion, 1-5% pigment, 0.2-1% wetting dispersant, 0.2-1% defoamer, 0.2-2% thickener, 0.1-1% pH adjuster, 0.1-0.2% bactericide preservative, 0.5-2% film-forming aid, 40-60% aggregate, and the balance is water;

[0008] The B component is low-alkali cement;

[0009] The weight ratio of component A to component B is (9.5-10.5):1.

[0010] By adopting the above technical scheme, pure acrylic emulsion is used as a film-forming substance, and additives such as wetting dispersants, defoamers, thickeners, pH regulators, bactericides and preservatives, and film-forming aids are used as functional additives to adjust the performance of the coating.

[0011] Low-alkali cement is used as component B and mixed with component A to prepare real stone paint. The inherent high strength and hardness characteristics of cement enable real stone paint to form a hard coating after curing. This coating can not only effectively resist the physical impact of the outside world, but also maintain the stability and durability of the coating. At the same time, the addition of cement also increases the viscosity of real stone paint, so that real stone paint can be better attached to the wall surface during construction, not easy to flow or drip, and improves construction efficiency and quality. Secondly, the hardening process of cement is a chemical reaction process, and its reaction speed is affected by many factors. The addition of cement in this application can indirectly adjust the curing speed of real stone paint. This helps construction personnel to better control the drying time and curing degree of the coating during construction, and ensures the quality of the coating. Finally, the addition of cement can prevent moisture from penetrating into the coating to a certain extent, enhance the waterproof performance of the coating, reduce the probability of the coating bulging and falling off under the scouring of rainwater, and protect the wall from the erosion of natural factors such as rainwater.

[0012] Furthermore, the aggregate is natural colored sand, including natural colored sand with a particle size of 40-80 mesh and natural colored sand with a particle size of 80-120 mesh.

[0013] Furthermore, the weight ratio of the natural colored sand with a particle size of 40-80 meshes to the natural colored sand with a particle size of 80-120 meshes is 1:(2-3).

[0014] By adopting the above technical solution, the aggregate is reasonably graded so that the aggregate particles inside the coating are evenly distributed, filling the pores and not easily absorbing water and swelling, thereby further improving the waterproof effect of the coating.

[0015] Furthermore, the aggregate is a modified aggregate whose surface has been modified by epoxy resin-siloxane hybrid polymer.

[0016] By adopting the above technical solution, epoxy resin-siloxane hybrid polymer is a new type of polymer material that combines the properties of epoxy resin and siloxane. It combines the mechanical strength, chemical resistance and adhesion of epoxy resin with the low surface energy of siloxane through chemical bonds to form a hybrid material with excellent comprehensive performance. Aggregates are modified with epoxy resin-siloxane hybrid polymers to form a waterproof layer on the surface of the aggregates. This waterproof layer can effectively block the penetration of water and reduce the absorption of water, thereby improving the waterproofness of the coating. At the same time, the compatibility of aggregates with pure acrylic emulsion can be improved, further improving the comprehensive performance of the coating.

[0017] Furthermore, the preparation method of the epoxy resin-siloxane hybrid polymer is:

[0018] 1) Prepolymerization

[0019] Dissolve polydimethylsiloxane and epoxy resin in a solvent, then add a catalyst, and react at 80-120°C for 2-4 hours to obtain a prepolymer;

[0020] 2) Curing reaction

[0021] Add a curing agent to the prepolymer and react at 120-180° C. for 2-6 hours to obtain an epoxy resin-siloxane hybrid polymer.

[0022] Furthermore, the epoxy resin is a perfluoropolyether modified epoxy resin, and the preparation method thereof is:

[0023] a) Activation of perfluoropolyether

[0024] Perfluoropolyether is added to a solvent to form a perfluoropolyether solution, and then sodium hydroxide and methanol are added to react at 50-60° C. for 2-4 hours to obtain hydroxy-perfluoropolyether;

[0025] b) Grafting reaction

[0026] Adding hydroxyl-perfluoropolyether into a solvent to form a hydroxyl-perfluoropolyether solution, then adding epoxy resin, reacting at 80-100° C. for 2-4 hours to obtain a reaction product;

[0027] c) Post-processing

[0028] The reaction product is washed and dried to obtain a perfluoropolyether modified epoxy resin.

[0029] By adopting the above technical scheme, hydroxyl groups are introduced into the perfluoropolyether through activation. The hydroxyl groups can undergo a ring-opening reaction with the epoxy groups of the epoxy resin to form ether bonds, thereby achieving grafting, and fluorine-modifying the epoxy resin to form a fluorocarbon chain structure. This structure has extremely low surface energy, thereby significantly improving the hydrophobicity of the material.

[0030] Fluorine modification is an effective method to improve the hydrophobicity of materials. By adding a certain amount of fluorine compounds to epoxy resin-siloxane hybrid polymers, a fluorocarbon chain structure can be formed. This structure has extremely low surface energy, thus significantly improving the hydrophobicity and oil resistance of the material.

[0031] Furthermore, the preparation method of the modified aggregate is: spraying the epoxy resin-siloxane hybrid polymer on the aggregate, so that the surface of the aggregate is covered with a layer of the epoxy resin-siloxane hybrid polymer.

[0032] Further, the wetting and dispersing agent is one of polycarboxylic acid-alkyl ammonium salt or unsaturated fatty acid polyamine amide;

[0033] The film-forming aid is one of ethylene glycol or dodecyl alcohol ester film-forming aids or a combination thereof;

[0034] The defoamer is selected from any one of silicone, mineral oil or polyether modified defoamers;

[0035] The thickener is one of a hydrophobically modified alkali swelling rheology regulator, a polyurethane thickener, a cellulose thickener, a bentonite thickener or a combination thereof.

[0036] The pH adjuster is any one of 2-amino-2-methyl-1-propanol, ammonia water, and dimethylethanolamine.

[0037] In a second aspect, the present application provides a method for preparing a two-component waterproof real stone paint, using the following technical solution.

[0038] A method for preparing a two-component waterproof real stone paint comprises the following steps:

[0039] S1. Mix and stir the pure acrylic emulsion, pigment, wetting dispersant, defoamer, thickener, pH adjuster, bactericide and preservative, film-forming aid, aggregate and water to obtain component A;

[0040] S2. Stir the low-alkali cement to obtain component B;

[0041] S3. Mix component A and component B according to the weight ratio and stir them evenly to obtain a two-component waterproof real stone paint. In summary, this application has the following beneficial effects:

[0042] 1. Use pure acrylic emulsion as film-forming material, and add low-alkali cement. The addition of mixed cement increases the viscosity of real stone paint, so that real stone paint can be better attached to the wall during construction, not easy to flow or drip, and improves construction efficiency and quality. Secondly, the hardening process of cement is a chemical reaction process, and its reaction speed is affected by many factors. The addition of cement in this application can indirectly adjust the curing speed of real stone paint. This helps construction personnel to better control the drying time and curing degree of the coating during construction and ensure the quality of the coating. Finally, the addition of cement can prevent moisture from penetrating into the coating to a certain extent, enhance the waterproof performance of the coating, reduce the probability of bulging and falling off of the coating under rain scouring, and protect the wall from erosion by natural factors such as rain. The water absorption of the obtained coating is as low as 1.02-0.01g / 2h, and the water resistance can reach 290-420h, and the alkali resistance can reach 102-120h.

[0043] 2. The aggregate is modified with epoxy resin-siloxane hybrid polymer to further improve the waterproof performance of the coating. The water absorption of the obtained coating is as low as 0.03-0.01g / 2h, the water resistance can reach 390-420h, and the alkali resistance can reach 120h. DETAILED DESCRIPTION

[0044] The present application is further described in detail below with reference to the embodiments.

[0045] Raw materials and intermediate preparation examples

[0046] raw material

[0047] Pure acrylic emulsion, brand BA201;

[0048] Pigments, rutile titanium dioxide;

[0049] Low alkali cement is white low alkali cement with a total alkali content of 0.5%, silicate cement;

[0050] Perfluoropolyether, brand FC-3135;

[0051] Epoxy resin, bisphenol A epoxy resin E-44.

[0052] Preparation Example

[0053] Preparation Example I

[0054] A perfluoropolyether modified epoxy resin, the preparation method of which is as follows:

[0055] a) Activation of perfluoropolyether

[0056] 1 kg of perfluoropolyether was added to 25 L of DMF solvent, and the solution was formed by stirring to dissolve the perfluoropolyether. Then, 0.075 kg of sodium hydroxide and 1 kg of methanol were added, and the reaction was carried out at 55° C. for 3 h to obtain hydroxy-perfluoropolyether.

[0057] b) Grafting reaction

[0058] Adding hydroxy-perfluoropolyether into 25 L of DMF solvent to form a hydroxy-perfluoropolyether solution, then adding 10 kg of epoxy resin, reacting at 90° C. for 3 h, to obtain a reaction product;

[0059] c) Post-processing

[0060] The reaction product is washed and dried to obtain a perfluoropolyether modified epoxy resin.

[0061] Preparation Example II-1

[0062] An epoxy resin-siloxane hybrid polymer, the preparation method of which is as follows:

[0063] 1) Prepolymerization

[0064] 30 kg of polydimethylsiloxane and 70 kg of epoxy resin were dissolved in toluene solvent, and then 1.5 kg of N, N-dimethylbenzylamine catalyst was added, and the mixture was reacted at 100° C. for 3 hours to obtain a prepolymer;

[0065] 2) Curing reaction

[0066] 1 kg of phthalic anhydride curing agent was added to the prepolymer and reacted at 150° C. for 4 hours to obtain an epoxy resin-siloxane hybrid polymer.

[0067] Preparation Example II-2

[0068] The difference from Preparation Example II-1 is that the epoxy resin is replaced by the perfluoropolyether-modified epoxy resin obtained in Preparation Example I.

[0069] Preparation Example III-1

[0070] A modified aggregate, the preparation method of which is as follows:

[0071] The epoxy resin-siloxane hybrid polymer obtained in Preparation Example II-1 was sprayed on the aggregate by a spraying device, and then dried at 70° C. to cover the surface of the aggregate with a layer of epoxy resin-siloxane hybrid polymer to obtain a modified aggregate.

[0072] Preparation Example III-2

[0073] Different from Preparation Example III-1, the epoxy resin-siloxane hybrid polymer in Preparation Example III-2 comes from Preparation Example II-2.

[0074] Preparation Example III-3

[0075] Different from Preparation Example III-1, in Preparation Example III-3, polydimethylsiloxane is used to replace the epoxy resin-siloxane hybrid polymer.

[0076] Example

[0077] Examples 1-3

[0078] A method for preparing a two-component waterproof real stone paint comprises the following steps:

[0079] S1. According to the raw material ratio in Table 1, pure acrylic emulsion, pigment, wetting dispersant, defoamer, thickener, pH adjuster, bactericidal preservative, film-forming aid, aggregate and water are mixed and stirred to obtain component A;

[0080] S2. Stir the low-alkali cement to obtain component B;

[0081] S3. Mix component A and component B in a weight ratio of 10:1 and stir evenly to obtain a two-component waterproof real stone paint.

[0082] Table 1 Example 1-3A component raw material ratio table (kg)

[0083] Example 1 Example 2 Example 3 Pure acrylic emulsion 30 35 40 pigment 5 3 1 Wetting and dispersing agents 0.2 0.6 1.0 Defoaming agent 1 0.6 0.2 Thickener 0.2 1.1 2.0 pH Adjusters 1.0 0.5 0.1 Bactericidal preservatives 0.1 0.2 0.2 Film-forming aids 0.5 1.0 2.0 aggregate 60 50 40 water 2.0 8.0 13.5

[0084] Among them, the pigment is rutile titanium dioxide, the wetting and dispersing agent is polycarboxylic acid-alkyl ammonium salt, the defoaming agent is a polyether modified defoaming agent, the thickener is a polyurethane thickener, the pH adjuster is 2-amino-2-methyl-1-propanol, the bactericidal preservative is a broad-spectrum bactericidal preservative based on isothiazolinone aqueous liquid, the film-forming aid is dodecanol ester, and the aggregate includes natural colored sand with a weight ratio of 1:2 of 40-80 mesh and natural colored sand with a particle size of 80-120 mesh.

[0085] Example 4

[0086] Different from Example 2, the aggregate in Example 4 includes natural colored sand with a particle size of 40-80 mesh and natural colored sand with a particle size of 80-120 mesh in a weight ratio of 1:3.

[0087] Example 5

[0088] Different from Example 2, the aggregate in Example 5 includes natural colored sand with a particle size of 40-80 mesh and natural colored sand with a particle size of 80-120 mesh in a weight ratio of 2:1.

[0089] Example 6

[0090] Different from Example 2, the aggregate in Example 6 is 2:1 40-80 mesh natural colored sand.

[0091] Example 7

[0092] Different from Example 2, the aggregate in Example 7 is natural colored sand with a particle size of 80-120 mesh.

[0093] Embodiment 8-10

[0094] Different from Example 2, in Examples 8-10, the aggregates were replaced with equal amounts of modified aggregates from Preparation Examples III-1 to III-3, respectively.

[0095] Comparative Example

[0096] Comparative Example 1

[0097] Different from Example 1, Comparative Example 1 does not include component B.

[0098] Performance Testing

[0099] The performance of the real stone paint and the real stone paint film in the embodiments and comparative examples was tested, and the test results are shown in Table 2 and Table 3.

[0100] Table 2 Performance test results

[0101]

[0102]

[0103] Table 3 Performance test results

[0104] Water absorption / g Water resistance / h Alkali resistance / h Example 1 0.06 330 108 Example 2 0.05 345 108 Example 3 0.06 335 108 Example 4 0.05 350 108 Example 5 0.08 310 102 Example 6 1.02 290 102 Example 7 1.00 295 102 Example 8 0.02 400 120 Example 9 0.01 420 120 Example 10 0.03 390 120 Comparative Example 1 2.30 240 96

[0105] The water absorption refers to the water absorption in two hours, and the water resistance and alkali resistance refer to the fact that there is no abnormality in the coating within the testing time.

[0106] It can be seen from Examples 1-10 and Table 2 that the basic properties of the real stone paint obtained in this application all meet the requirements.

[0107] Combining Examples 1-10 with Comparative Example 1 and Table 3, it can be seen that the water absorption of the real stone paint obtained in Examples 1-10 is lower than that in Comparative Example 1, and the water resistance and alkali resistance of the real stone paint obtained in Examples 1-10 are better than those in Comparative Example 1, which indicates that the comprehensive performance of the real stone paint prepared in the present application is better.

[0108] Combining Example 1 with Comparative Example 1 and Table 3, it can be seen that the water absorption of the real stone paint obtained in Example 1 is lower than that of Comparative Example 1, and the water resistance and alkali resistance of the real stone paint obtained in Example 1 are better than those of Comparative Example 1, which shows that the addition of low-alkali cement can reduce the water absorption of the coating and improve the water resistance of the coating. This may be because cement itself has good waterproof properties, and the addition of cement can prevent water from penetrating into the coating to a certain extent, enhance the waterproof performance of the coating, reduce the probability of bulging and falling off of the coating under rain scouring, and protect the wall from erosion by natural factors such as rain.

[0109] Combining Example 2 with Example 4-7 and Table 3, it can be seen that the water absorption of the real stone paint obtained in Example 2 and Example 4 is lower than that in Example 5-7, and the water resistance and alkali resistance of the real stone paint obtained in Example 2 and Example 4 are better than those in Example 5-7, which shows that the gradation of the aggregate affects the waterproof performance of the coating, and the aggregate gradation in Example 2 and Example 4 is better. This may be because the aggregate gradation defined in this application makes the aggregate particles inside the coating evenly distributed, fills the pores, is not easy to absorb water and swell, and further improves the waterproof effect of the coating.

[0110] In combination with Example 2 and Example 8-10, and in combination with Table 3, it can be seen that the water absorption of the real stone paint obtained in Example 2 is higher than that of Example 8-10, and the water resistance and alkali resistance of the real stone paint obtained in Example 2 are lower than those of Example 8-10, which shows that surface modification of aggregate can further improve the waterproof performance of coating, and the modification method in Example 9 is more excellent. The chemical resistance of epoxy resin and the low surface energy of siloxane are combined together by chemical bonds to form a hybrid material with excellent comprehensive performance. Aggregate is modified with epoxy resin-siloxane hybrid polymer, and a waterproof layer can be formed on the surface of aggregate. This waterproof layer can effectively block the penetration of water and reduce the absorption of water, thereby improving the waterproofness of coating. At the same time, the compatibility of aggregate and pure acrylic emulsion can be improved, further improving the comprehensive performance of coating. And epoxy resin is fluorine-modified to form a fluorocarbon chain structure, which has an extremely low surface energy, thereby significantly improving the hydrophobicity of the material.

[0111] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A two-component waterproof real stone paint, comprising component A and component B, characterized in that: The component A comprises the following raw materials in weight percentage: 30-40% pure acrylic emulsion, 1-5% pigment, 0.2-1% wetting dispersant, 0.2-1% defoamer, 0.2-2% thickener, 0.1-1% pH adjuster, 0.1-0.2% bactericide and preservative, 0.5-2% film-forming aid, 40-60% aggregate, and the balance is water; The B component is low-alkali cement; The weight ratio of component A to component B is (9.5-10.5):

1.

2. A two-component waterproof real stone paint according to claim 1, characterized in that: The aggregate is natural colored sand, including natural colored sand with a particle size of 40-80 meshes and natural colored sand with a particle size of 80-120 meshes.

3. A two-component waterproof real stone paint according to claim 2, characterized in that: The weight ratio of the natural colored sand with a particle size of 40-80 meshes to the natural colored sand with a particle size of 80-120 meshes is 1:(2-3).

4. A two-component waterproof real stone paint according to claim 1, characterized in that: The aggregate is a modified aggregate whose surface is modified by epoxy resin-siloxane hybrid polymer.

5. A two-component waterproof real stone paint according to claim 4, characterized in that: The preparation method of the epoxy resin-siloxane hybrid polymer is: Prepolymerization Dissolve polydimethylsiloxane and epoxy resin in a solvent, then add a catalyst, and react at 80-120°C for 2-4 hours to obtain a prepolymer; Curing reaction Add a curing agent to the prepolymer and react at 120-180° C. for 2-6 hours to obtain an epoxy resin-siloxane hybrid polymer.

6. A two-component waterproof real stone paint according to claim 5, characterized in that: The epoxy resin is a perfluoropolyether modified epoxy resin, and the preparation method thereof is as follows: a) Activation of perfluoropolyether Perfluoropolyether is added to a solvent to form a perfluoropolyether solution, and then sodium hydroxide and methanol are added to react at 50-60° C. for 2-4 hours to obtain hydroxy-perfluoropolyether; b) Grafting reaction Adding hydroxyl-perfluoropolyether into a solvent to form a hydroxyl-perfluoropolyether solution, then adding epoxy resin, reacting at 80-100° C. for 2-4 hours to obtain a reaction product; c) Post-processing The reaction product is washed and dried to obtain a perfluoropolyether modified epoxy resin.

7. A two-component waterproof real stone paint according to claim 5, characterized in that: The preparation method of the modified aggregate is: spraying the epoxy resin-siloxane hybrid polymer on the aggregate to cover the surface of the aggregate with a layer of the epoxy resin-siloxane hybrid polymer.

8. The two-component waterproof real stone paint according to claim 1, characterized in that: The wetting and dispersing agent is one of polycarboxylic acid-alkyl ammonium salt or unsaturated fatty acid polyamine amide; The film-forming aid is one of ethylene glycol or dodecyl alcohol ester film-forming aids or a combination thereof; The defoamer is selected from any one of silicone, mineral oil or polyether modified defoamers; The thickener is one of a hydrophobically modified alkali swelling rheology regulator, a polyurethane thickener, a cellulose thickener, a bentonite thickener or a combination thereof.

9. A two-component waterproof real stone paint according to claim 8, characterized in that: The pH adjuster is any one of 2-amino-2-methyl-1-propanol, ammonia water, and dimethylethanolamine.

10. A method for preparing a two-component waterproof real stone paint according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Mix and stir the pure acrylic emulsion, pigment, wetting dispersant, defoamer, thickener, pH adjuster, bactericide and preservative, film-forming aid, aggregate and water to obtain component A; S2. Stir the low-alkali cement to obtain component B; S3. Mix component A and component B according to the weight ratio and stir them evenly to obtain a two-component waterproof real stone paint.

Citation Information

Patent Citations

  • Water-borne epoxy resin and super-amphiphobic coat as well as preparation method and application of water-borne epoxy resin and super-amphiphobic coat

    CN103408705A

  • Super-amphiphobic surface with universality and its preparation method

    CN103709882A

  • Lacquer for construction in low temperature and high humidity condition and preparation method thereof

    CN105295606A

  • Organic-inorganic composite decorative anti-alkali waterproof integrated coating and preparation method thereof

    CN107955472A

  • Preparation method and application of water-soluble hydrophobic-oilphobic modification material

    CN109593392A